Canada's Civil–Military Seminar: An Approach to Narrowing the Civil–Military Gap. Issue 3 (July 2019) - Thompson, Megan M.; Hendriks, Tonya; Piasentin, Kelly; Holton, Tara; Febbraro, Angela; Gill, Ritu
The "civil–military gap" is a significant factor that can hinder the success of complex comprehensive approach missions. Perhaps nowhere is this gap more apparent than in the relationship between military and civilian nongovernmental organizations. Interagency education and training have been suggested as ways to diminish this divide. This research describes one Canadian approach to interagency education: the Civil–Military Seminar. Quantitative and qualitative results demonstrate the promise of both the assessment approach used and the positive outcomes that may help to narrow the civil–military gap.